Density Functional Theory Studyof Water Adsorption on the CoO (100) and CoO (110) Surfaces - Azemi, Salihah; Arifin, Khuzaimah; Mohamad Yunus, Rozan; Timmiati, Sharifah Najiha (International Journal of Integrated Engineering, 2019)
The density functional theory (DFT) method was used in this study to determine the chemical and physical properties of Cobalt Oxide (CoO) because it is a reliable, fast and inexpensive technique. This study is designed to determine the electronic properties of CoO bulk and the adsorption energy of the water molecule (H2O) on the CoO surface. CoO crystals used in this study have been optimized by using the GGA-PBE and LDA-CAPZ methods. The study found that calculations using GGA-PBE were closer to the experiment value. Without considering spin orbital interactions, CoO showed a metallic electronic band structure. After considering the spin orbital interaction calculation, each alpha and beta band structures has band gap of 1.55 eV, which is similar to the reported theoretical value. The ground state of CoO is antiferromagnetic base-on alpha and beta band structures. The peak absorption of light representing optical properties at wavelength energy is 351 nm in visible light spectrum (UV) range. The DFT calculation is used to determine the H2O adsorption energy to the surfaces of CoO (100) and CoO (110). H2O adsorption energy on CoO (100) and CoO (110) surfaces is based on eight different configurations, with different H2O adsorption positions on each CoO surface. On the CoO (100) surface, H2O adsorption energy is optimum in Model 5, with a value of 5.123 eV. Meanwhile, the H2O adsorption energy on the CoO (110) surface is optimum in Model 6, with a value of 2.810 eV. Based-on adsorption energy study, it expected that H2O easier to absorb on CoO(110) rather than on CoO(100).